2011
DOI: 10.1111/j.1440-1800.2011.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Technological Intimacy in Haemodialysis Nursing

Abstract: BENNETT PN. Nursing Inquiry 2011; 18: 247-252 Technological intimacy in haemodialysis nursing Technology plays a major role in nursing care. Among the challenges for nurses is being able to maintain a patient focus while surrounded by highly complex technology. The provision of high quality nursing care in technologically complex environments is particularly challenging when nurses develop relationships with their patients over an extended period of time. In these environments the potential for intimate relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 31 publications
2
60
0
2
Order By: Relevance
“…All this is congruent with the views of certain authors. For example, according to Bennett (2011), as HD nurses work in a technical care environment, they must develop both technical and interpersonal skills in order to offer quality care in their particular clinical context. This author has specified also that the technical dimension is only one part of care, not all of it.…”
Section: Discussion Intervention Feasibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…All this is congruent with the views of certain authors. For example, according to Bennett (2011), as HD nurses work in a technical care environment, they must develop both technical and interpersonal skills in order to offer quality care in their particular clinical context. This author has specified also that the technical dimension is only one part of care, not all of it.…”
Section: Discussion Intervention Feasibilitymentioning
confidence: 99%
“…Similarly, in a study by Moran, Scott, and Darbyshire (2009), patients undergoing HD remarked that their interactions with nurses were very superficial and centered primarily on their physical assessment at the expense of their needs, values, and expectations. According to Bennett (2011), this contributed to dehumanised care. This worrisome situation underscores the urgency for nurses to adhere to humanistic values, particularly those associated with Watson's (2008Watson's ( , 2012 theory of human caring, in order to offer person-centered care, including to patients undergoing HD sensitive to the quality of human relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers and theorists (Almerud, Alapack, Fridlund & Ekebergh, 2008;Barnard, 2002;Barnard & Sandelowski, 2001;Bennett, 2010Bennett, , 2011Bevan, 1998Bevan, , 2000McGibbon & Peter, 2008;Poland et al, 2005;Sandelowski, 2002;Tranter et al, 2009;Wynn, 2002;Zitzelsberger, 2004) have called for more research to investigate the nature and effects of technologies in and on specific places of care. Some studies explored nurses' views (Bull & FitzGerald, 2006;Marck, 2000;McGibbon & Peter, 2008;Tranter et al, 2009) and Allen et al (2011) andNagle (1998) identified the need to investigate similarities and differences between care recipients' and providers' perspectives of technologies and their settings.…”
Section: Discussionmentioning
confidence: 99%
“…The patients preferred to establish friendly relationships with their nurses. In a hemodialysis department, the patients and the nurses are in contact with each other for many years, which encourages the establishment of friendly relationships (27). The patients expressed their desire to have capable nurses take care of them and teach them empowering techniques (28).…”
Section: Competent Staffmentioning
confidence: 99%